2014
DOI: 10.1007/s00125-014-3293-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium–vitamin D co-supplementation on glycaemic control, inflammation and oxidative stress in gestational diabetes: a randomised placebo-controlled trial

Abstract: Aims/hypothesis This study was designed to assess the effects of calcium and vitamin D supplementation on the metabolic status of pregnant women with gestational diabetes mellitus (GDM). Methods This randomised placebo-controlled trial was performed at maternity clinics affiliated to Kashan University of Medical Sciences, Kashan, Iran. Participants were 56 women with GDM at 24-28 weeks' gestation (18 to 40 years of age). Subjects were randomly assigned to receive calcium plus vitamin D supplements or placebo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
112
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 38 publications
6
112
3
3
Order By: Relevance
“…Patients with GDM are susceptible to insulin resistance and increased lipid profiles (Asemi, Karamali, & Esmaillzadeh, 2014).Our study demonstrated that GDM patients who received zinc supplements for 6 weeks had significant decreases in FPG, serum insulin concentrations, HOMA-IR, and HOMA-B and a significant rise in QUICKI compared with the placebo. Few studies have evaluated the effects of zinc administration on FPG and markers of insulin resistance in patients without GDM.…”
Section: Discussionmentioning
confidence: 64%
“…Patients with GDM are susceptible to insulin resistance and increased lipid profiles (Asemi, Karamali, & Esmaillzadeh, 2014).Our study demonstrated that GDM patients who received zinc supplements for 6 weeks had significant decreases in FPG, serum insulin concentrations, HOMA-IR, and HOMA-B and a significant rise in QUICKI compared with the placebo. Few studies have evaluated the effects of zinc administration on FPG and markers of insulin resistance in patients without GDM.…”
Section: Discussionmentioning
confidence: 64%
“…However, some reports have shown that Ca and vitamin D supplementation did not affect pregnancy outcomes in mothers without GDM (14,15) . Vitamin D and Ca might affect pregnancy outcomes through influencing skeletal composition and smooth muscle strength (13) as well as metabolic profiles (16) . Ca and vitamin D have been suggested to act jointly rather than independently.…”
mentioning
confidence: 99%
“…Meanwhile, our results showed that calcium supplementation significantly reduced blood glucose and serum insulin levels, and improved glucose tolerance and insulin sensitivity in HFD-fed mice. Similarly, the beneficial effects of dietary calcium on glycemic control has been indicated in many studies [16,18,38]. However, consumption of high calcium provided no effect on glycemic control in overweight patients with type 2 diabetes [17].…”
Section: Discussionmentioning
confidence: 99%